An investigation of Li-decorated N-doped penta-graphene for hydrogen storage. (21st July 2021) - Hao, Jinbo; Wei, Feng; Zhang, Xinhui; Li, Long; Chen, Changcheng; Wu, Ge; Wu, Liyuan; Liang, Dan; Ma, Xiaoguang; Lu, Pengfei; Song, Haizhi
Abstract: By making use of first principles calculations, lithium-decorated (Li-decorated) and nitrogen-doped ( N -doped) penta-graphene (PG) was investigated as a potential material for hydrogen storage. The geometric and electronic structures of two types of N -doped PG were studied, and the band gaps were 1.86 eV and 2.06 eV, respectively, depending on the positions of the substitution. The probable adsorption sites for Li atoms on topside and downside were calculated. Hydrogen molecules were added one by one to Li-decorated N -doped PG to research the maximum hydrogen gravimetric density. It is found that up to 5 hydrogen molecules on topside and 8 hydrogen molecules on downside can be adsorbed around a Li atom, and the average adsorption energies are in the range of physical adsorption processes (0.1–0.4 eV). The gravimetric densities can reach 7.88 wt% for N -doped PG with Li decoration. Our results suggest that Li-decorated N -doped PG is a significantly promising material for hydrogen storage. Highlights: The stability of two types of Li-decorated N -doped PG were studied. Li-decorated N -doped penta-graphene is a potential material for hydrogen storage. The hydrogen storage capacities can reach 7.88 wt%, which is higher than the values of other carbon-base materials.